Pengaruh Strategi Pembelajaran KooperatifThink Pair Share (Tps) Dan Project Based Learning(Pjbl) Terhadap Hasil Belajar MatematikaDitinjau Dari Komunikasi Siswa Di Smp Negeri 1Kartasura - Madyawati, Dyah Tara, Dr. Slamet H.W, M.Pd (2016)
The research is conducted to know: (1) the significant effect of learning strategy Think Pair Share and Project Based Learning in mathematics learning outcomes, (2) the significant effect of communication in mathematics learning outcomes, (3) interaction between of learning strategy Think Pair Share and Project Based Learning and communication in mathematics learning outcomes. The research is a quasi-experimental research. The population of research is all of the 7th grades of Junior High School in N 1 Kartasura in academic years of 2015/2016. There are two classes used as sampling is class VIIG and VIIH. The technique of sampling is random sampling. The technique of collection data are test, questionnaire, and documentation. Technique of analyzing data used analysis of variance two different cells. The research result show that: (1) there is significant efeect of learning strategy in mathematics learning outcomes i.e FA = 12.80 > Ftabel = 4.01, (2) there is a significant effect of communication inmathematics learning outcomes i.e FB = 7.82 > Ftabel = 3.16, (3) there is no interaction between learning strategy and communication in mathematics learning outcomes i.e FAB = 0.51 < Ftabel = 3.16.